Amphiphilic polymers: structure-activity relationship between their properties and interactions with cell membranes - Schiazza, Lorenzo (2022)
Polymers are extensively employed in drug delivery for a wide variety of purposes; specifically, the use of drug delivery systems which include bioadhesive polymers has been investigated for decades. Whilst there have been recent examples of phospholipid and cholesterol-based amphiphilic polymers for drug delivery and cell membrane modification purposes, no drug formulation based on membrane-inserting polymers has proven successful when applied in vivo to more complex systems. An important aspect of this PhD work is that, although its overall aim was to design membrane-inserting polymers for drug encapsulation and release, it allowed for a thorough investigation of the interactions between membrane-inserting polymers and lipid bilayers. This aspect is critical for further progress in the membrane-binding polymers field, as no previous study has conducted a systematic investigation on the effect that polymers with membrane inserting chain-ends have when they associate with lipid bilayer membrane. Accordingly, this PhD work describes the design, synthesis and characterisation of polymers presenting different membrane components such as cholesterol, a 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) phospholipid, at their alpha chain end, or multiple units of long fatty acid chains. These polymers were synthesised by reversible addition−fragmentation chain-transfer (RAFT) polymerisation with different chain lengths and by employing hydrophilic and functional monomers, to produce tools to explore polymer-membrane interaction. We demonstrated that amphiphilic polymers containing cell membrane lipids at their polymer chain-end readily interacted with lipid bilayer membranes, as confirmed by a range of in vitro experiments. Conversely, analogous hydrophilic control polymers missing those functional chain-ends showed a negligible degree of interaction with these membranes. Further elucidation of the mechanisms, kinetics and thermodynamics of these processes was achieved by investigating the interaction of the described polymers with synthetic model membranes. This thesis work further expanded on this aspect by also including an initial in silico modelling of these phenomena, providing an initial understanding of these polymer-membrane interactions. These also provide a structure-function relationship for the membrane-inserting materials synthesised in terms of their effect on membrane fluidity, kinetics and thermodynamics of membrane association and dissociation. As membrane-binding polymers could help retention of formulations in vivo following oral administration, we worked on two potential delivery systems. We first focused on nitrofurantoin, an antibiotic used to treat infections in the urinary tract with a fast intestinal absorption and fast elimination. The encapsulation experiments for this drug were based on the formation of an ionic interaction between the acid-bearing polymers and the drug, which contains a basic nitrogen atom. This approach yielded promising initial results, but inconsistencies in terms of reproducibility prompted the adoption of covalent drug encapsulation. For this purpose, we used mesalazine, an immunomodulatory drug employed in the treatment of inflammatory bowel diseases. We synthesised a mesalazine-bearing N-alkyl acrylamide monomer and employed this novel monomer to produce drug-conjugated polymers. The membrane-interacting polymers loaded with mesalazine were still able to interact with membranes and showed a pH-dependent drug release.